O2-S4.03 The cost-effectiveness of human papillomavirus vaccination of females over age 12 years in the USA. (10th July 2011) - Chesson, H; Markowitz, L
Abstract : Background: Although the recommended age for Human Papillomavirus (HPV) vaccination of females is 11 to 12 years in the USA, catch-up" vaccination is recommended for females aged 13–26 years who have not been previously vaccinated. The objective of this study was to evaluate the cost-effectiveness of catch-up vaccination strategies for females aged 13–30 years in the USA. Method: We revised and updated a previously-published, spreadsheet-based model of HPV vaccination to estimate the costs and benefits of female HPV vaccination. The health outcomes we included were: cervical intraepithelial neoplasia, genital warts, recurrent respiratory papillomatosis, and HPV associated cancers (cervical, vaginal, vulvar, anal, oropharyngeal, and penile). We examined the cost-effectiveness of catch-up vaccination for three age groups: ages 13–21 years, ages 21–26 years, and ages 27 to 30 years. We examined a 100-year time horizon. Routine vaccination of 12 year olds was assumed to occur in all 100 years, with coverage set at 20%, 30%, or 75%. The annual probability of receiving catch-up vaccination was 5% for ages 13 to 18 years and 1.25% for ages 19 years and older. The duration of the catch-up vaccination program was varied from 1 to 20 years. Results: Catch-up vaccination generally became less cost-effective as routine coverage increased and as the duration of the catch-up program increased. When vaccine coverage and the duration of the catch-up program were varied (and all other parameters were set to their base case values), the incremental cost per QALY gained by extending the duration of catch-up vaccination ranged from 5000 to 40 000 for ages 13 to 21, from 50 000 to 85 000 for ages 21 to 26, and was >140 000 for ages 27 to 30 years. The relatively favourable cost-effectiveness ratios for vaccination of ages 13 to 21 years and the relatively unfavourable cost-effectiveness ratios for vaccination of ages 27 to 30 years were consistent regardless of routine vaccine coverage and the duration of the catch-up vaccine program. Conclusion: Our preliminary findings support the current recommendations of the Advisory Committee on Immunisation Practices (ACIP) for female vaccination. However, although catch-up vaccination for ages 21 to 26 years might be considered cost-effective now, the cost per QALY gained by catch-up vaccination may increase as time goes by and as vaccine coverage increases.